Factors Associated with Telemedicine Services Provision for Sexually Transmitted Disease Diagnosis and Treatment Among Dermatologists: Evidence from China - Yingzhe Yu; Zhuo Chen; Jing Zhang; Ping Zhou; Lingyi Lu; Bingjiang Lin; Yang Li (Telemedicine Reports, 2022)
Background: Telemedicine has experienced rapid growth in China, with wide applications for chronic disease management. Objective: This study examined a unique survey dataset to identify the provision of telemedicine services by dermatologists, and to explore its association with physician characteristics, perception of diagnosis, and physicians' perceptions of the advantages and disadvantages of telemedicine. Materials and Methods: Responses to an anonymous voluntary questionnaire were collected from 238 dermatologists in Zhejiang Province, China, via a mixed mode of online and in-person data collection. Data were analyzed using Stata 16.0. Empirical analyses utilized descriptive statistics and multivariable logistical regression. Results: Among a total of 238 physicians, 34.9% provided telemedicine services. Results from the multivariable logistic regression indicated that, if physicians can use their spare time to help patients, seniority and their perception of the benefit of telemedicine are the two most important factors determining their likelihood of providing telemedicine services among the studied sample. Conclusion: Telemedicine holds great promise, but its practices need to be more efficient to save time and reduce the risk of misdiagnosis so that more physicians may participate.